Hyperoxia decreases glycolytic capacity, glycolytic reserve and oxidative phosphorylation in MLE-12 cells and inhibits complex I and II function, but not complex IV in isolated mouse lung mitochondria. - Kumuda C Das (Public Library of Science (PLoS), 2013)
High levels of oxygen (hyperoxia) are frequently used in critical care units and in conditions of respiratory insufficiencies in adults, as well as in infants. However, hyperoxia has been implicated in a number of pulmonary disorders including bronchopulmonary dysplasia (BPD) and adult respiratory distress syndrome (ARDS). Hyperoxia increases the generation of reactive oxygen species (ROS) in the mitochondria that could impair the function of the mitochondrial electron transport chain. We analyzed lung mitochondrial function in hyperoxia using the XF24 analyzer (extracellular flux) and optimized the assay for lung epithelial cells and mitochondria isolated from lungs of mice. Our data show that hyperoxia decreases basal oxygen consumption rate (OCR), spare respiratory capacity, maximal respiration and ATP turnover in MLE-12 cells. There was significant decrease in glycolytic capacity and glycolytic reserve in MLE-12 cells exposed to hyperoxia. Using mitochondria isolated from lungs of mice exposed to hyperoxia or normoxia we have shown that hyperoxia decreased the basal, state 3 and state3 μ (respiration in an uncoupled state) respirations. Further, using substrate or inhibitor of a specific complex we show that the OCR via complex I and II, but not complex IV was decreased, demonstrating that complexes I and II are specific targets of hyperoxia. Further, the activities of complex I (NADH dehydrogenase, NADH-DH) and complex II (succinate dehydrogenase, SDH) were decreased in hyperoxia, but the activity of complex IV (cytochrome oxidase, COX) remains unchanged. Taken together, our study show that hyperoxia impairs glycolytic and mitochondrial energy metabolism in in tact cells, as well as in lungs of mice by selectively inactivating components of electron transport system.